Armenian communities of the Northeastern Mediterranean - Hovannisian, Richard G. (Mazda Publishers, 2016)
Armenian communities of the northeastern Mediterranean / Richard G. Hovannisian – Armenian settlements in the Antioch region / Hagop Tcholakian – Armenian Musa Dagh in the nineteenth and early twentieth century / Vahram L. Shemmassian – The significance of un-making M-G-M's The forty days of Musa Dagh / Ara Soghomonian – Armenians, Alawites, and the Alexandretta crisis (1937-1939) / Keith David Watenpaugh – The oral tradition of Musa Dagh / Sona Zeitlian – Culture and personality : the case of Anjar / Herant Katchadourian – The popular folklore of Musa Dagh Armenians : synchronous and diachronic changes / Verjiné Svazlian – Vakef Köy of Musa Dagh : the sole Armenian village remaining in Turkey / Vahram L. Shemmassian – Schools and orphanages of Dört-Yol/Chork-Marzban / Vera Sahakyan – The Chork-Marzban/Dört-Yol Armenians : three episodes of self-defense / Minas Kojayan – Oral testimony as source material for the history of Kessab (1909-1922) / Sèda Mavian – Kessab as a diasporan community / Hagop Tcholakian – Paradise lost and regained in Kessab : narratives of rebuilding and migration / Susan Pattie – The battle for Kessab / Charles Glass
Includes bibliographical references and index
Keywords: Armenians; Yoghun Oluk Region (Turkey); Villages; Community life